« Typen », maître-mot du design industriel - Gwenaëlle Bertrand; Maxime Favard (Appareil)
In one of his major texts entitled Principles of Bauhaus production (Grundsätze der Bauhausproduktion), Walter Gropius set out the role of design workshops in demonstrating the social necessity of producing with the avant-garde tools of industry. From the utensil to the home, it was total modernity that he aspired to. The workshops-laboratories (Laboratoriumswerkstätten) then became the place where technique, economy and invention were brought together. The embodiment of this modernity took the form of a search for “Typen”—“types” in French—but systematically translated by “standards”, thus depriving us of its disciplinary stake. From then on, these misunderstandings in the translation from German into French led to a devaluation of the epistemological value of the term that we now wish to re-establish in this work of reappropriating “Typen”, the key word that marks the origin of industrial design.